A Case of Sarcoidosis Diagnosed by the Progression of Stenosis of the Proximal Bronchi - Hanzawa, Satoshi; Kawahara, Tatsuo; Nukui, Yoshihisa (The Journal of the Japan Society for Respiratory Endoscopy, 2024)
Background. Sarcoidosis with stenosis of the proximal bronchi is rare. Case. A 71-year-old woman was referred to our hospital due to mediastinal lymphadenopathy in year X-4. Endobronchial ultrasound-guided transbronchial needle aspiration of the mediastinal lymph nodes was performed; however, no definitive diagnosis was made, and follow-up was continued. From year X-2, dyspnea on exertion appeared. From year X-1, obstructive ventilatory impairment developed. She was treated for bronchial asthma and her symptoms showed slight improvement. In February of year X, chest computed tomography (CT) showed thickening of the bronchovascular bundle of both segmental bronchi on the proximal side, and bronchoscopy was performed to conduct a detailed examination. The right B2, left upper division bronchus, and left B6 were obstructed. Examination of a biopsy specimen obtained from the right B2 revealed non-caseating granuloma. Based on chest CT findings, and the pathological findings of the bronchial biopsy, a diagnosis of sarcoidosis was made. Therapy with prednisolone (15 mg) was initiated, and her respiratory symptoms and obstructive ventilatory impairment markedly improved. The improvement of bronchial obstruction was also confirmed by bronchoscopy. Conclusion. We should consider sarcoidosis with stenosis of the bronchi and actively perform bronchoscopy for the diagnosis of patients with progressive obstructive ventilatory impairment.